Financial Performance Analysis in PT. Bayan Resources Tbk 2020-2022 Period - Annisa Fajariah Damanik; Riska Franita (International Journal of Society and Law, 2024)
When investing capital, financial performance must be analyzed first by investors by carrying out financial analysis by calculating ratios. In this research, the ratios used include current ratio, quick ratio, debt to total assets, debt to equity, ROA, ROE, inventory turnover and total asset turnover. The aim of this research was to understand and analyze the financial performance of PT Bayan Resources Tbk in the 2020-2022 period based on liquidity, solvency, profitability and activity ratios. The analytical method used in this research is descriptive qualitative. The results of the research conducted state that PT Bayan Resources Tbk has the ability to cover its short- term liabilities by managing total current assets and capital owned, the company can also generate increased profits by managing assets and capital and the company is not yet able to manage total assets that can generate sales.